Why associations matter : the case for First Amendment pluralism - Sheahan, Luke C. (University Press of Kansas, 2020)
"First Amendment rights are hailed as the hallmark of the American constitutional system, protecting religious liberty, freedom of speech, freedom of the press, and freedom of association from government interference. In Christian Legal Society v. Martinez (2010), however, the Supreme Court demoted freedom of association in the panoply of First Amendment rights. This decline in protection for freedom of association has broad ramifications for the constitutional status of voluntary associations in civil society. Why Associations Matter examines how a fundamental right disappeared from the Supreme Court's reasoning and draws on the political sociology of Robert Nisbet to develop a theoretical framework for bolstering freedom of association in American constitutionalism. Luke Sheahan shows that the case law from NAACP v. Alabama (1958) through Boy Scouts v. Dale (2000) has recognized free association only as an individual right of expressive association derived from the Speech Clause alone. This pattern in Supreme Court jurisprudence culminated in Martinez, in which the Supreme Court refused to uphold the associational right of a student group at a public university to police its own membership based upon the purpose of the group. Sheahan argues that the association case law is flawed at a fundamental level and turns to Nisbet, whose sociological work exposes the problem with a focus on the state and individual to the neglect of nonpolitical associations and institutions"--